Necesidad de reformar el artículo 265 del código orgánico integral penal, en cuanto a la sanción establecida, a efecto de garantizar la debida proporcionalidad entre la infracción penal y la sanción - Aguilar Sotomayor, Marlo Fernando (2016)
The art. 1 of our Constitution determines to Ecuador in a Constitutional State of Rights and Social Justice, guarantor of the rights of persons. To forewarn these rights or recognized in the Constitution of the Republic of Ecuador legal rights, criminal law should seek puno balance between the protection of these rights and the power to the State to punish, limiting the right to punish. Therefore, criminal law should determine the limits to avoid falling into private vengeance, nor impunity. The offense is unlawful conduct which violates a specific legal interest in the Constitution and protected by the criminal law. The criminal law has apparently contradictory double role against the rights of individuals. On the one hand, it protects rights and, secondly, restricts. From the perspective of the victims, it protects them when one has been seriously injured. From the person who is in conflict with the law, you may exceptionally restrict their rights if a person violates the rights of others and justifies the application of a sanction. Our Comprehensive Organic Code of Criminal Procedure, is weak with the strong and strong with the weak, many of the criminalized offenses are not proportional with the punishment. Proportionality is an instrument of judicial measures restricting fundamental rights. It is the most important principle of constitutional law, which applies clearly, through rules that constitute a system of precise controls assessment constitutionality of measures restricting fundamental rights to declare unconstitutional or eventual declaration of constitutional admissibility, the which will generate greater justice and greater enjoyment of fundamental rights, which constitute one of the pillars of the legal system in a Constitutional State of rights and justice. One of the fundamental guarantees of due process, the penalties are consistent with the principle of proportionality, ie, there must be some consistent relationship between the degree of impairment of a right and severity of the penalty.